6-(4z-9)=9-5z

Simple and best practice solution for 6-(4z-9)=9-5z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(4z-9)=9-5z equation:


Simplifying
6 + -1(4z + -9) = 9 + -5z

Reorder the terms:
6 + -1(-9 + 4z) = 9 + -5z
6 + (-9 * -1 + 4z * -1) = 9 + -5z
6 + (9 + -4z) = 9 + -5z

Combine like terms: 6 + 9 = 15
15 + -4z = 9 + -5z

Solving
15 + -4z = 9 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
15 + -4z + 5z = 9 + -5z + 5z

Combine like terms: -4z + 5z = 1z
15 + 1z = 9 + -5z + 5z

Combine like terms: -5z + 5z = 0
15 + 1z = 9 + 0
15 + 1z = 9

Add '-15' to each side of the equation.
15 + -15 + 1z = 9 + -15

Combine like terms: 15 + -15 = 0
0 + 1z = 9 + -15
1z = 9 + -15

Combine like terms: 9 + -15 = -6
1z = -6

Divide each side by '1'.
z = -6

Simplifying
z = -6

See similar equations:

| 16x^2+58x+51=0 | | 15x^2+32x+9=0 | | 11x^3-59x^2+23x-1=0 | | 4x^2-8x-192=0 | | 7y^2+10y+10=74 | | 18+n-7= | | 2(x-1)+7=-6 | | 5/4*25/1 | | x/2+3=2x/5 | | -7z=-56 | | -4.9x^2+4.9x+.8=1.829 | | 20+5/2r=-20 | | log[5](x+18)+log[5](x-6)=2*log[5](x) | | 10x^2+67x+99=0 | | 0=-y^2+100y+10000 | | x-3/3=x-5/5 | | 28x^2-3x-91=0 | | 9v^3-36v=0 | | 3/4+4y=6y-3/4 | | 4x^2+41x+45=0 | | w^2+6w-280=0 | | -.5(32x^2)+64x+0=-200 | | x=0.01 | | 10+x/6=10-x/9 | | 3x+(75/x)=0 | | x^2+23x+90=0 | | X(X+4)=113 | | 2x+5=58 | | x/2-=5 | | -1/6+y=-4/5 | | -4/7+y=-3/5 | | 18a^2+4-[6(a^2-2)+5]= |

Equations solver categories